Empowering Urban Women through Community-Based Culinary Education - Mustangin; Riska Dewi Yuli Rahmi; Saraka; Hepy Tri Winarti (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
The main problem in this study is the limited access of homemakers in urban areas to life skills empowerment programs relevant to their families' economic needs. Furthermore, existing training programs are not fully aligned with the community's real needs and are not supported by professional training institutions. This study aims to analyze the implementation of community-based training for homemakers in improving life skills. This study used a qualitative approach. The subjects were homemakers participating in community-based culinary training in Samarinda City, as well as the training organizers. Data collection methods included interviews, observation, and documentation, using interview guidelines and observation sheets as instruments. Data analysis techniques were carried out through the stages of data reduction, data presentation, and conclusion. The results showed that the training implementation began with identifying community needs, followed by partnerships with Course and Training Institutions (LKP) to provide competent instructors, implementation of learning using lecture and practice methods, and evaluation of learning through observation. The implications of this study indicate that community-based training designed to meet the real needs of the community and supported by partnerships with training institutions has the potential to improve homemakers' life skills and economic independence. Thus, community-based culinary education can be an effective and sustainable strategy for empowering urban women.